Online misinformation can distort witnesses’ memories. Analysis of co-witness discussions using an online version of the MORI-v technique - Kękuś, Magdalena; Szpitalak, Malwina; Polczyk, Romuald; Barzykowski, Krystian (Frontiers in Psychology, 2024)
Introduction The memory conformity effect occurs when people witness a given incident and then talk to each other about it, and the statement of one person affects the memory account of another person with respect to that incident. The main objectives of this experiment were (1) to examine the effectiveness of a modified version of the MORI-v technique in inducing the memory conformity effect and (2) to investigate how the manner in which participants discuss the observed event influences the magnitude of this effect. In general, the modified online MORI-v technique consists of the following main elements: (1) original material, that is, two versions of a short film which are identical except for certain critical details; for example, in one version, a thief puts on a red cap, but in the other version it is black; (2) the collaborative recognition test, that is, a discussion about the original material which leads to mutual misinformation; and (3) an individual recognition test that checks the effect of the discussion on the memory account of the original material. Methods A total of 72 participants (36 pairs) aged 18–54 took part in the research. Participants were tested using the online MORI-v technique: They were familiarized with the original material on their computers at home, and then they talked about it via a video communication app and completed an individual recognition test on their computers. Importantly, the discussions were recorded and analyzed in detail after the experimental session. Results and discussion Using the online MORI-v technique, the effect of memory conformity was demonstrated, that is, in the individual recognition test, the proportion of correct answers to questions about discussed details (related to misinformation) was lower than the proportion of correct answers to questions about non-discussed details. It was also demonstrated that if one participant introduced misinformation during the discussion about a particular item and the other did not question it, the latter’s answer to that item during the individual recognition test was most often incorrect. However, if one participant introduced misinformation during the discussion about an item and the other questioned it, the latter’s answer about that item during the individual recognition test was most often correct.